Hubungan antara Regulasi Emosi dengan Problematic Internet Use pada Siswa SMA - Anika, Suci Oktavia; Kurniawan, Rizal (Al-DYAS, 2024)
Problematic Internet Use is a problem caused by internet access. In this study, high school students access the internet for various things such as access to communication services, learning media, online games, short video access and entertainment. Emotional regulation is considered as one of the factors causing Problematic Internet Use in high school students. The purpose of this study was to determine the relationship between emotional regulation and Problematic Internet Use among high school students in West Sumatra. This study uses quantitative methods with a correlational approach. The subjects in this study amounted to 285 people obtained using purposive sampling method. The measuring instrument used to measure Problematic Internet Use is the GPIUS 2 scale, while to measure emotional regulation using the ERQ scale. The analysis technique used the Spearman Rank test. So that the results of the analysis show that there is a significant relationship with a negative correlation value of -0.415 between the emotion regulation variable and the PIU variable. The negative correlation results indicate an unidirectional relationship between the emotion regulation variable and PIU, which indicates that when emotion regulation increases, PIU will decrease.